Pengaruh Kesadaran Wajib Pajak dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Saleh Suku; Maryoni Stevanny Kainama; Theodora Florence Tomasoa (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
his study aims to analyze the influence of taxpayer awareness and tax sanctions on motor vehicle taxpayer compliance at SAMSAT Waihaong, Ambon City. The research employs a quantitative method with a survey approach. Data were collected through structured questionnaires distributed to 100 randomly selected respondents using a simple random sampling technique. Data analysis was conducted using multiple linear regression. The results indicate that taxpayer awareness (X1) and tax sanctions (X2) have a positive and significant effect on taxpayer compliance (Y). The regression equation obtained is Y = 0.738 + 1.222X1 + 0.128X2, with a coefficient of determination (R²) value of 0.853. This shows that taxpayer awareness and tax sanctions together explain 85.3% of the variability in taxpayer compliance, while the remaining 14.7% is influenced by other factors. Taxpayer awareness has a more dominant effect than tax sanctions, with coefficients of 1.222 and 0.128, respectively. This study recommends enhancing public outreach and education about the benefits of taxes and enforcing clear and firm sanctions to encourage taxpayer compliance. These findings provide significant contributions to tax management in regions with unique socio-economic characteristics such as Ambon City